2016
DOI: 10.1037/pas0000329
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Dyadic Coping Inventory with Chinese couples: Factorial structure, measurement invariance, and construct validity.

Abstract: The Dyadic Coping Inventory (DCI, Bodenmann, 2008) assesses how couples support each other when facing individual (e.g., workload) and common (e.g., parenting) stressors. Specifically, the DCI measures partners' perceptions of their own (Self) and their partners' behaviors (Partner) when facing individual stressors, and partners' common coping behaviors when facing common stressors (Common). To date, the DCI has been validated in 6 different languages from individualistic Western cultures; however, because cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 48 publications
8
82
0
Order By: Relevance
“…The findings of the present study indicated configural invariance (same items are associated with the same factors across gender), metric invariance (factor loadings for all the items are equivalent across gender), and scalar invariance (item intercepts are invariant for men and women). These results are consistent with the ones of previous DCI validation studies that have found MI across gender in samples from the United States, Romania, and China (Randall, Hilpert, Jimenez‐Arista, Walsh, & Bodenmann, ; Rusu et al, ; Xu et al, ). DCIFS assesses the same construct for men and women, and the gender differences found are determined by the real differences in DCIFS scales and not by the construct measurement differences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the present study indicated configural invariance (same items are associated with the same factors across gender), metric invariance (factor loadings for all the items are equivalent across gender), and scalar invariance (item intercepts are invariant for men and women). These results are consistent with the ones of previous DCI validation studies that have found MI across gender in samples from the United States, Romania, and China (Randall, Hilpert, Jimenez‐Arista, Walsh, & Bodenmann, ; Rusu et al, ; Xu et al, ). DCIFS assesses the same construct for men and women, and the gender differences found are determined by the real differences in DCIFS scales and not by the construct measurement differences.…”
Section: Discussionsupporting
confidence: 91%
“…Except for the validation of the 44‐item DCI in French and Italian (Ledermann et al, ), validation studies of the DCI in other languages used the 37‐item version. Validation studies were conducted in Chinese (Xu, Hilpert, Randall, Li, & Bodenmann, ), English (Levesque, Lafontaine, Caron, & Fitzpatrick, ; Randall, Hilpert, Jimenez‐Arista, Walsh, & Bodenmann, ), Greek (Roussi & Karademas, ), Japanese (Yokotani & Kurosawa, ), Portuguese (Vedes, Nussbeck, Bodenmann, Lind, & Ferreira, ), Romanian (Rusu, Hilpert, Turliuc, & Bodenmann, ), and Spanish (Falconier, Nussbeck, & Bodenmann, ). Some validation studies were conducted with couples (Falconier et al, ; Martos, Sallay, Nistor, & Józsa, ; Rusu et al, ; Xu et al, ; Yokotani & Kurosawa, ) whereas others have been conducted with individuals (Bodenmann, ; Ledermann et al, ; Levesque et al, ; Randall et al, ; Vedes et al, ).…”
Section: The DCImentioning
confidence: 99%
“…The English validation of the DCI in the Canadian population (Levesque et al 2014) confirmed the five-factor structure of DC by Self and by Partner (SC, emotion-focused SDC, problem-focused SDC, DDC, and NDC) and the one-factor structure of CDC. Validation studies in Spanish, Persian, Romanian, Portuguese, and Chinese (Falconier et al 2013a;Fallahchai et al 2017;Rusu et al 2016;Vedes et al 2013;Xu et al 2016) showed the same five-factor solution for the DC by Self and Partner and a two-factor solution for CDC (problem-focused CDC and emotion-focused CDC). In all these studies the DCI comprised very good validity.…”
Section: The Factorial Structure Of the Dyadic Coping Inventory (Dci)mentioning
confidence: 92%
“…In all these studies the DCI comprised very good validity. Furthermore Xu et al (2016) compared 5 + 2-factor and 4 + 1-factor models within three cultural groups. The results confirmed that the five-factor solution for DC by Self and by Partner and the two-factor solution for CDC appeared to the most appropriate in terms of model fit and consistency across the analyses, hence Polish validation studies was decided to test 5-factor structure of DC by Self and by Partner and 2-factor solution for CDC.…”
Section: The Factorial Structure Of the Dyadic Coping Inventory (Dci)mentioning
confidence: 99%
See 1 more Smart Citation